Ivermectin use on pastured livestock in Colombia: parasite resistance and impacts on the dung community - Villar, David; Schaeffer, David J (Revista Colombiana de Ciencias Pecuarias, 2022)
Ivermectin (IVM) has been the most widely used antiparasitic agent in veterinary medicine since it came to the market in 1981. In its risk assessment, the American Food and Drug Administration (FDA) determined that, although it is very toxic to aquatic organisms, it is unlikely to contaminate watercourses from current applications registered for animal use. However, the effects of IVM on non-target invertebrate fauna can greatly impact grassland ecology. The economic loss from undegraded dung on lowering the quality of pastures and reducing the area of pasture available and palatable to livestock was US $380 million for the American economy in 2003. We discuss selected aspects of IVM effects on non-target species, dung beetles in pastures. We do not consider confined or feedlot production. Ivermectin affects a highly beneficial and taxonomically diverse group inhabiting dung pats, including flies, parasitic wasps, and coprophilus and predatory dung beetles. Some studies show that dung from IVM-treated animals can remain in the pasture without noticeable signs of degradation for up to 340 days, while pats from untreated animals are almost completely degraded after 80 days. Field and laboratory studies have shown many invertebrates species are susceptible to IVM at concentrations well below those excreted in the feces of treated cattle. IVM affects reproduction and development of coleopteran larvae at concentrations up to 10 times lower that cause mortality. In Colombia, at least 68 species of the subfamily Scarabaeinae have been identified in dung communities. Greater diversity of dung beetles is associated with forests and silvopastoral systems that incorporate native trees and provide habitats for survival. IVM should be used selectively on animals on pasture to minimize parasite resistance and effects on dung beetle communities and other nontarget invertebrate communities.